Search for quantum black hole production in high-invariant-mass lepton+jet final states using pp collisions at √s=8 TeV and the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; Abouzeid, O S; Abramowicz, H; Abreu, H; et al. (Physical review letters, 2014)
This Letter presents a search for quantum black-hole production using 20.3 fb-1 of data collected with the ATLAS detector in pp collisions at the LHC at √s = 8 TeV. The quantum black holes are assumed to decay into a final state characterized by a lepton (electron or muon) and a jet. In either channel, no event with a lepton-jet invariant mass of 3.5 TeV or more is observed, consistent with the expected background. Limits are set on the product of cross sections and branching fractions for the lepton+jet final states of quantum black holes produced in a search region for invariant masses above 1 TeV. The combined 95% confidence level upper limit on this product for quantum black holes with threshold mass above 3.5 TeV is 0.18 fb. This limit constrains the threshold quantum black-hole mass to be above 5.3 TeV in the model considered.
Keywords: Electrons; elektrony; Elementary Particles; Quantum Theory; Models, Theoretical; teoretické modely; Mesons; mezony; elementární částice; kvantová teorie